2003
DOI: 10.1128/iai.71.12.7069-7078.2003
|View full text |Cite
|
Sign up to set email alerts
|

Disruptionof Cell Polarity by Enteropathogenic Escherichia coli EnablesBasolateral Membrane Proteins To Migrate Apically and ToPotentiate PhysiologicalConsequences

Abstract: Enteropathogenic Escherichia coli (EPEC) disrupts the structure and barrier function of host intestinal epithelial tight junctions (TJs). The impact of EPEC on TJ "fence function," i.e., maintenance of cell polarity, has not been investigated. In polarized cells, proteins such as ␤ 1 -integrin and Na ؉ /K ؉ ATPase are restricted to basolateral (BL) membranes. The outer membrane EPEC protein intimin possesses binding sites for the EPEC translocated intimin receptor (Tir) and ␤ 1 -integrin. Restriction of ␤ 1 -i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 37 publications
1
89
1
Order By: Relevance
“…17,18 During infection, β 1 -integrin relocalizes from the basolateral to the apical membrane to interact with bacterial intimin, which is essential for disruption of intestinal barrier function. 19 This study demonstrates that PEG decreases the amount of β 1 -integrin in intestinal epithelia and that pretreatment with PEG is sufficient to reduce attachment of C. rodentium. It has been demonstrated that high-molecular weight PEG inhibits the attachment of Pseudomonas to host cells by forming a physical barrier between the bacteria and host cells; 32 however, this type of PEG is not for systemic oral use.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…17,18 During infection, β 1 -integrin relocalizes from the basolateral to the apical membrane to interact with bacterial intimin, which is essential for disruption of intestinal barrier function. 19 This study demonstrates that PEG decreases the amount of β 1 -integrin in intestinal epithelia and that pretreatment with PEG is sufficient to reduce attachment of C. rodentium. It has been demonstrated that high-molecular weight PEG inhibits the attachment of Pseudomonas to host cells by forming a physical barrier between the bacteria and host cells; 32 however, this type of PEG is not for systemic oral use.…”
Section: Discussionmentioning
confidence: 67%
“…We showed that low-molecular weight PEG downregulates β 1 -integrin, a host cell surface receptor critical for A/E pathogen attachment. [16][17][18][19] Pretreatment of colonic epithelia with PEG, concurrent presence of PEG during infection, or PEG treatment after the start of infection decreases the attachment of C. rodentium to colonic epithelia. We also presented evidence that PEG attenuates EGFR signaling and improves clinical signs of disease in mouse colon infected with C. rodentium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon EPEC infection, basolateral b 1 -integrin moves to the apical side of enterocytes where it can interact with intimin. 50 Although Tir remains essential for bacterial attachment, cytoskeletal rearrangement, and barrier defects, the interaction of b 1 -integrin with intimin further enhances the attachment of EPEC to IECs and is required for maximal decreases in TER. 50 It should be noted that certain gastrointestinal pathogens, such as the parasite Giardia lambia, are known to modulate epithelial permeability through the induction of apoptosis.…”
Section: Disruption Of Epithelial Barrier Structure and Functionmentioning
confidence: 99%
“…50 Although Tir remains essential for bacterial attachment, cytoskeletal rearrangement, and barrier defects, the interaction of b 1 -integrin with intimin further enhances the attachment of EPEC to IECs and is required for maximal decreases in TER. 50 It should be noted that certain gastrointestinal pathogens, such as the parasite Giardia lambia, are known to modulate epithelial permeability through the induction of apoptosis. 51,52 As mentioned before, EPEC induces apoptosis in infected IECs in a caspase-dependent manner.…”
Section: Disruption Of Epithelial Barrier Structure and Functionmentioning
confidence: 99%